Financiamento à inovação no nordeste: um mapeamento a partir de programas do governo federal (2008-2013) - Silva, Allisson Nascimento Gonçalves da (2015)
The innovation process is very complex, expensive and demand substantial volume of resources, Besides, the degree of uncertainty that pervades is high. Is completely essential to the role of the financial system as a promoter of investment for companies-j. a. Schumpeter was who stressed the importance of credit with a fundamental element of the development process, which is responsible for an advance of purchasing power to businessmen, who use it for innovative activities-however, when it comes to investments for innovation becomes a more complex mechanism. It is in this context that this dissertation intends to perform a contextualization of public sources of financing to technological innovation, through governmental programmes of support to Brazilian companies in the Northeast, which stands out for its high innovative potential and a Regional System of Innovation in consolidation phase. We highlight sources such as FINEP, CNPQ, BNB, BNDES and MCTI. The data shows that, with regard to the institutional environment of innovation, three States are highlighted, namely: Bahia, Pernambuco and Ceará, and this is reflected on the funding of the programmes. However, there is still much room for improvement when compared with the more developed region of the country – the Southeast.